Ridge Tillage Improves Soil Properties, Sustains Diazotrophic Communities, and Enhances Extensively Cooperative Interactions Among Diazotrophs in a Clay Loam Soil - Hu, Xiaojing; Liang, Aizhen; Yao, Qin; Liu, Zhuxiu; Yu, Zhenhua; Wang, Guanghua; Liu, Junjie (Frontiers in Microbiology, 2020)
Reduced tillage practices (such as ridge tillage, RT) have been potential solutions to the weed pressures of long-term no-tillage (NT) and the soil intensive disturbances caused by conventional tillage (such as moldboard plow tillage, MP). Although soil diazotrophs are significantly important in global nitrogen (N) cycling and contribute to the pool of plant-available N in agroecosystems, little is currently known about the responses of diazotrophic communities to long-term different tillage practices. In current study, we investigated the differences among the effects of NT, RT and MP on soil properties, diazotrophic communities and co-occurrence network patterns in bulk and rhizosphere soils under soybean grown in a clay loam soil of Northeast China. The results showed that RT and MP led to higher contents of total C, N and available K compared to NT in both bulk and rhizosphere soils, and RT resulted in higher soybean yield than NT and MP. Compared to NT and RT, MP decreased the relative abundances of free-living diazotrophs while promoted the growth of copiotrophic diazotrophs. Little difference of diazotrophic community diversity, composition and community structure were detected between RT and NT, but MP obviously decreased diazotrophic diversity and changed the diazotrophic communities in contrast to NT and RT in bulk soils. Soil nitrogenous nutrients had negative correlations with diazotrophic diversity and significantly influenced diazotrophic community structure. Across all diazotrophic networks, the major diazotrophic interactions transformed into cooperatively dominated network under RT with more intense and efficient interactions among species than NT and MP. Overall, our study suggested that RT with minor soil disturbances could stabilize diazotrophic diversity and communities as NT and possessed highly positive interactions among diazotrophic species relative to NT and MP.